Melatonin Interaction Resulting in Severe Sedation - Brian C Foster; Kosta Cvijovic; Heather S Boon; Teresa W Tam; Rui Liu; Mano Murty; Duc Vu; Walter Jaeger; Ross T Tsuyuki; Joanne Barnes; Sunita Vohra (Frontiers Media S.A., 2015)
Purpose. Natural health products (NHPs), including melatonin, are widely used products. Despite the widespread assumption that all NHPs are safe, they contain pharmacologically active substances and can therefore have adverse effects and/or interact with pharmaceuticals. Objective: To investigate the mechanism underlying NHP interactions identified through the Pharmacy SONAR active surveillance study. Methods: Active surveillance was undertaken in community pharmacies to identify adverse events in patients who had recently taken NHPs together with conventional pharmaceuticals. For suspected NHP-pharmaceutical interactions, the possible mechanism of action was explored by in vitro analysis of samples of different products to identify cytochrome P450 enzyme (CYP) inhibition potential. Results: Active surveillance identified a 19-year-old male taking citalopram, nortriptyline and oxycodone concomitantly and who experienced severe sedation when melatonin was added to this regimen. In vitro analysis involving several melatonin products showed product-dependent inhibition of CYP1A2, CYP2C19 and CYP3A7. Conclusion: The adverse event was likely due to a primary pharmacokinetic interaction between melatonin and citalopram; although mechanistically, interactions affecting cytochrome P450-mediated metabolism may have occurred with all of these health products. A pharmacodynamic interaction may also be possible, but beyond the capacity of this study to establish. Key words: Melatonin, citalopram, nortriptyline, oxycodone, drug interaction.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.